Comparison factors between synthetic and natural textile dyes - García Mora , Angela
Most of the dyes used in the textile industry are of synthetic origin: dense and toxic chemicals, obtained from petroleum derivatives by polluting processes, highly soluble in water, highly resistant to the action of chemical agents and not very biodegradable (EPA, 1997). The objective of the work that the INTEX seedbed of the Textile and Leather Manufacturing Center - Regional Capital District (CMTC) has been developing during the year 2022 is to compare natural textile dyes with synthetic dyes based on technical parameters and their impacts on the environment. and the health of dry-cleaning workers in the fashion system in the Bogotá Region. Until now, dyeing tests have been carried out in parallel with dyes of natural and synthetic origin on different types of fibers and fabrics, the evaluation of each sample will continue and, together with the observations and measurements obtained, an analysis table is expected to be obtained. comparison that allows members of the Bogotá Region fashion system to decide the type of coloring according to their specific requirements.